A Comparative Study Between the Paradigmatic Models of Girls and Boys in the Formation Process of Marriage Trauma - Shadmand, Samaneh; Hashemianfar, Seyed Ali; Aghasi, Saeid (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: This study aimed to compare the paradigmatic models of girls and boys in the formation process of marriage trauma using a grounded theory framework. Methods and Materials: This qualitative study employed the systematic grounded theory approach of Strauss and Corbin. Semi-structured, in-depth, face-to-face interviews were conducted with 21 unmarried girls and 17 unmarried boys residing in Shahreza who did not have psychological disorders. Participants were recruited through an Instagram call posted by a psychological clinic and selected via snowball sampling. Interviews lasted 60–80 minutes and explored causal conditions, contextual conditions, intervening conditions, strategies, and consequences related to fear of marriage. Data were analyzed through open, axial, and selective coding to identify core categories and reconstruct gender-specific paradigmatic models explaining marriage trauma. Findings: The analysis revealed distinct gendered pathways in the formation of marriage trauma. For girls, the core category was “the ambiguity of the value of marriage and perfectionism of self and parents,” arising from emotional failures of others, familial expectations, religious–moral incongruence, and economic insecurity. For boys, the core category was “the meaninglessness of marital authenticity,” driven by fear of unsuccessful marriage, economic instability, perceived legal vulnerability, past relational hurt, and sociocultural constraints. Across both groups, intervening conditions such as parental conflict, emotional dependency, and intergenerational narratives intensified trauma trajectories. Strategies included seeking emotional reassurance, emphasizing compatibility, and attempting to learn communication skills; however, consequences such as increased dependency, avoidance, and loss of perceived marriage opportunities were evident. Conclusion: Marriage trauma among youth arises from intertwined emotional, familial, sociocultural, and structural factors, with clear gender-specific mechanisms shaping fear and avoidance of marriage; understanding these paradigmatic models can inform culturally responsive interventions and support systems.